TECHNOLOGY - BASED PRACTICES AND TEACHERS’ INSTRUCTIONAL EFFECTIVENESS IN AGRICULTURAL SCIENCE IN UPPER BASIC SCHOOLS IN ABIA STATE, NIGERIA - Ogbeyealu, Okafor Jane; Anyanwu, Blessing Uchechi (Journal of Continuing and Development Education, 2025)
This study examined influence of Technology-Based Practices and Teachers’ Instructional Effectiveness in Agricultural Science in Upper Basic Schools in Abia State, Nigeria. The study adopted survey research design. Three specific objectives, research questions and Hypotheses guided the study. A population of 2176 male and female Agricultural Science teachers at Upper Basic School, made up of 937 male teachers and 1239 female teachers was used. The sample for this study was 253 Agricultural teachers which comprised 113 male teachers and 240 female teachers. Multi stage sampling procedure was used. The instruments for data collection were a 15-item researcher’s developed questionnaire titled: Technology-Based Practices in Upper Basic Schools’ Agricultural Science Questionnaire (TBPUBSASQ). The reliability of the instruments was determined using Cronbach alpha statistic which yielded an overall index value of .745. Mean values were used to analyze research questions, standard deviation measured data dispersion and a t-test examined null hypotheses at a 0.05 significance level. The results showed among others that teachers’ use of classroom management systems, educational apps and technology-based practices influenced the teaching of Agricultural science Education in Upper Basic Schools in Abia State. It was recommended among others that school management should consider integrating more technology-based practices into Agricultural Science education instruction to enhance teachers’ instructional effectiveness.